2017
DOI: 10.1111/papt.12154
|View full text |Cite
|
Sign up to set email alerts
|

The role of cognitive and metacognitive factors in non‐clinical paranoia and negative affect

Abstract: Metacognitive beliefs may be an important determinant of negative affect in the context of non-clinical paranoia. The consideration of both cognitive and metacognitive factors may be helpful when working with people with distressing paranoid ideas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Although the outcomes of this study may have provided more nuanced results, the findings of the current article are in line with research using the ASQ, and the broader attributional styles literature. Negative affect (Sellers et al, 2018 ), threat sensitivity (Freeman, 2007 ), low self‐esteem (Bentall et al, 1994 ), and disruptions to interpersonal functioning (Hajdúk et al, 2019 ) have been related to paranoia pathology, and reflect important constructs for future studies to capture.…”
Section: Discussionmentioning
confidence: 99%
“…Although the outcomes of this study may have provided more nuanced results, the findings of the current article are in line with research using the ASQ, and the broader attributional styles literature. Negative affect (Sellers et al, 2018 ), threat sensitivity (Freeman, 2007 ), low self‐esteem (Bentall et al, 1994 ), and disruptions to interpersonal functioning (Hajdúk et al, 2019 ) have been related to paranoia pathology, and reflect important constructs for future studies to capture.…”
Section: Discussionmentioning
confidence: 99%
“…At the end of our analysis, we came across the fact that-as conjecturedmany of the 18 most common EMSs, analyzed by the YSQ-SF3, were strongly associated with drunkorexia in its various aspects. These results were not surprising, owing to the fact that maladaptive cognitive schemas-concretized by a mode of selfdestructive fundamental relations and constituting a functional compensation for an unmet basic emotional need during childhood-are transfigured into a maladaptive, irrepressible, and incompetent defense mechanism if they are maintained to adulthood (Schenck, 2012). As a consequence, the individual would engage in toxic behaviors, seeking protection from any perception in front of which he/she recognizes himself unfit to cope.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, emotional discomfort and schema activation can lead to maladaptive relationships with oneself and others (Young, 1999). Indeed, within the literature, negative cognitive schemas have been associated with a broad array of harmful mental health outcomes, namely negative affect and depressive/anxiety symptoms (Bredicean et al, 2020;Faustino et al, 2022;Sellers et al, 2018), and particularly among individuals with substance use disorders (Shorey et al, 2015). To illustrate, within our present study, six EMSs (i.e., emotional deprivation, subjugation, failure, abandonment, mistrust, and social isolation) showed significant positive statistical correlations with drunkorexia scores.…”
Section: Discussionmentioning
confidence: 99%
“…Delusional beliefs, such as paranoid ideas, have been documented as being linked with negative emotional states and unhelpful thinking patterns (Freeman, Garety, Kuipers, Fowler, & Bebbington, 2002). A recent study found that metacognitive beliefs may determine negative affective states in non-clinical paranoia (Sellers, Emsley, Wells, & Morrison, 2018). Another important element is the poor insight which is frequently reported in individuals with psychosis (Lincoln, L€ ullmann, & Rief, 2007) and constitutes a major obstacle for treatment (Lysaker, Vohs, Hillis, et al, 2013b).…”
Section: Practitioner Pointsmentioning
confidence: 99%